Satellite observations of interaction between tropics and mid-latitudes - KALSI , S.R.; HALDER , S. R. (MAUSAM, 1992)
In certain seasons and over certain locations, the mid-latitude westerlies invade subtropical and tropical areas. Short wave perturbations moving in the broad mid-latitude westerlies amplify the. long wave troughs creating new baroclinic zones in relatively southern latitudes. These. baroclinic zones Interact .with the low-latitude circulations thus leading to development of new circulation pattern .In which low level easterlies extend northward over the Peninsula, central and northwest .India. The paper describes the role of short waves in the interaction between tropics and mid-latitudes and presents satellite data of a few sequences In which such Interactions have actually taken place.